ИНГЛИС ТИЛ БИЛИМИНДЕ ФРАЗЕМАЛАРДЫҢ ИЗЕРТЛЕНИЎИ ҲӘМ ОЛАРДЫҢ РУС ТИЛ БИЛИМИНЕ ТӘСИРИ - Торебаева, Ф.Қ. (SCIENCE and SOCIETY, 2022)
The article considers the points of view of linguists regarding the classification of the semantic structure of phrasemes, which can also include the gender component. The gender component of phraseme semantics can participate both in explicit and implicit form. The article provides examples of phrases with a gender component.
Keywords: gender; sex; linguistics; androcentrism; explicit; implicit; frame; idiom; gender component